Intensive immunosuppression followed by autologous hematopoietic stem cell transplantation for the treatment of multiple sclerosis. (June 2020) - Lycke, Jan; Lenhoff, Stig
Autologous hematopoietic stem cell transplantation (AHSCT) to treat multiple sclerosis (MS) has mostly been used in devastating cases as the last option to stop further neurological deterioration. However, evidence from several retrospective clinical trials indicates that young, less disabled patients with highly inflammatory active MS are the most likely to benefit from AHSCT, and after moving from high-intensity to nonmyeloablative procedures the tolerability of AHSCT has increased and its associated risk and mortality have declined considerably. Recent meta-analyses and randomized clinical trials show that AHSCT is more effective than currently approved disease-modifying therapies (DMTs), with suppression of disease activity in 70–90% of patients and long-term cessation of disease activity in two-thirds of treated patients. The rationale for AHSCT is to eliminate autoimmunity and achieve immune resetting by intense immunosuppression followed by infusion of autologous hematopoietic stem cells. Similar effects on the immune system have been suggested for cladribine and alemtuzumab treatment and, together with AHSCT, they constitute the induction or immune-reconstitution therapies for MS. Although, further randomized controlled trials of AHSCT for MS are needed, it has become clear that improved patient selection and lower intensity conditioning regimens have reduced AHSCT associated risks and mortality and strengthened the position of AHSCT among other DMTs. Do we have enough experience and scientific support for AHSCT in MS to move from an exclusive treatment for aggressive, treatment-resistant MS and acquire broader indications, similar to other effective DMTs?